2021
DOI: 10.1186/s41687-021-00296-z
|View full text |Cite
|
Sign up to set email alerts
|

Does scrolling affect measurement equivalence of electronic patient-reported outcome measures (ePROM)? Results of a quantitative equivalence study

Abstract: Background Scrolling is a perceived barrier in the use of bring your own device (BYOD) to capture electronic patient reported outcomes (ePROs). This study explored the impact of scrolling on the measurement equivalence of electronic patient-reported outcome measures (ePROMs) in the presence and absence of scrolling. Methods Adult participants with a chronic condition involving daily pain completed ePROMs on four devices with different scrolling pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…The benefits of BYOD studies are multifarious; the approach allows participants to use their own technologies, leading to better compliance [ 9 , 10 ] and, potentially, less chance of introducing biases, such as the Hawthorne effect, from monitoring technologies [ 11 ]. For participants, there is a familiarity with and access to the technology they use in their daily lives [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The benefits of BYOD studies are multifarious; the approach allows participants to use their own technologies, leading to better compliance [ 9 , 10 ] and, potentially, less chance of introducing biases, such as the Hawthorne effect, from monitoring technologies [ 11 ]. For participants, there is a familiarity with and access to the technology they use in their daily lives [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Remote PRO data capture can facilitate real-time understanding of a treatment’s safety and effectiveness by measuring symptoms and functional impacts in the participant’s usual environment instead of solely within a clinical setting [ 6 ]. Within the clinical trials industry, administering PRO instruments electronically (electronic patient-reported outcomes/ePRO) has become commonplace [ 7 9 ], especially when collecting data remotely at defined time points as it enables assurance of the contemporaneousness of the data. In addition, remote data capture can reduce both site and participant burden by enabling reduced frequency and duration of face-to-face clinic visits [ 3 ]; thus, offering the opportunity to facilitate increased adoption of the decentralized trial (DCT) model and enhance patient-centricity in clinical trials.…”
mentioning
confidence: 99%
“…Historically, participants have been provisioned devices solely for the completion of ePROs. However, in recent years there has been increased interest in taking advantage of the option for participants to use their own device (smartphone, tablet, laptop) for completing study questionnaires—known as ‘bring-your-own-device’ (BYOD) [ 7 ].…”
mentioning
confidence: 99%
See 2 more Smart Citations